Patient perceptions of cognitive screening in adult audiology services: A qualitative exploration - Broome, Emma E.; Tannirandorn, Puntrika; Straus, Jean; Beale, Phoebe; Heffernan, Eithne; Dening, Tom; Henshaw, Helen (Frontiers in Neurology, 2023)
Introduction Both hearing loss and dementia are extremely pervasive, especially amongst older adults. As hearing loss and dementia have common symptoms, misdiagnosis can be common, and failure to address hearing loss for people with dementia could accelerate cognitive decline. The timely detection of cognitive impairment is clinically important, however the use of cognitive assessments in adult audiology services is a hotly debated topic. Although the early detection of cognitive impairment may improve patient care and quality of life, patients attending audiology services for hearing assessment might not expect to be asked questions about their cognition. The aim of this study was to qualitatively explore patient and public perspectives and preferences on the use of cognitive screening within adult audiology services. Methods Quantitative and qualitative data were gathered from an online survey and a workshop. Descriptive statistics were applied to quantitative data and an inductive thematic analysis was performed on free-text responses. Results In total, 90 respondents completed the online survey. Overall, cognitive screening in audiology was reported to be acceptable to participants (92%). A reflexive thematic analysis of the qualitative data reported four themes: i) knowledge of cognitive impairment and screening, ii) implementation of cognitive screening, iii) impact of screening on patient and iv) contributions to future care and research. A workshop was held with five participants to discuss and reflect on the findings in more detail. Discussion Participants found cognitive screening to be acceptable within adult audiology services providing audiologists had suitable training, and sufficient explanation and justification were provided. However, implications such as additional time and staff resource and supplementary training for audiologists would be required to address participants concerns.